(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
All about the one billion people work in the agricultural sector, constituting approximately 28 per cent of the employed population. About 450 million are waged workers, many of whom depend on incomes from jobs in the plantation sector. While the share of employment in agriculture has declined in many central Asian countries due to technological advancements and economic shifts, it remains a critical sector for livelihoods, food security, and rural development. This hard-working community have often received little recognition for their critical work in food production. Offers equal importance to agricultural labourers, just as we do to farmers, is crucial for a more equitable and sustainable agricultural system. Besides, the land ownership, in many cases, the line between smallholder farmers and agricultural labourers can be quite blurry. Both groups are often deeply intertwined in the agricultural ecosystem, and their roles can overlap. In practice, many smallholder farmers also work as agricultural labourers, especially when their farming operation doesn’t provide enough income year-round. Adopting similar policies for agricultural labourers as those for farmers would ensure that the people who are essential to food production receive fair compensation, protection, and support. A more equitable policy approach would enhance agricultural productivity, promote rural development, and improve the livelihoods of millions of workers who are often overlooked. This would create a more sustainable and inclusive agricultural system that benefits everyone involved. Bureaucrats or stakeholders writing policies with no experience in farming directly or indirectly.